Effect of adalimumab on joint disease: features of patients with psoriatic arthritis detected by magnetic resonance imaging. Issue 01 (9th February 2009) - Anandarajah, A P; Ory, P; Salonen, D; Feng, C; Wong, R L; Ritchlin, C T
Abstract : Background: Bone marrow oedema (BMO), synovitis, effusion and joint erosion on magnetic resonance imaging (MRI) may be used as outcome measures in psoriatic arthritis (PsA). Objective: To assess the impact of adalimumab on BMO, synovitis, effusion and erosions in PsA, as measured by MRI. Methods: Fifteen patients with active PsA (⩾3 tender and ⩾3 swollen joints) were enrolled in an open-label pilot study. Each received adalimumab subcutaneously every other week for 24 weeks. MRI was obtained at baseline and 24 weeks. Results: MRI was available for 11 patients, pre and post-therapy. BMO and effusion scores improved markedly after 24 weeks of adalimumab, while no significant change was noted in erosion score. An unanticipated finding, however, was the lack of improvement in the MRI synovitis score. Conclusions: Improvement in BMO and unchanged erosion scores may explain the "anti-erosive" effects of adalimumab in PsA. Persistence of BMO and synovitis on MRI suggests ongoing disease activity and supports the continuation of long-term anti-TNF therapy.